Effect of Microfinance on Vulnerability, Poverty and Risk in Low Income Households - Ranjula Bali Swain; Maria Floro (Uppsala University, Department of Economics, 2007)
Uncertainty and unpredictability faced by low-income households increase their vulnerability making poverty even more unbearable. Indias National Bank for Agriculture and Rural Development (NABARD)-initiated Self-Help Group (SHG) program, which is currently the largest and fastest growing microfinance program in the developing world, has been aggressively promoted as a way of combating poverty. This paper investigates whether or not SHG participation results in reducing poverty and vulnerability. A theoretical framework is developed to examine the mechanisms through which the pecuniary and non-pecuniary effects of the SHG program on the beneficiaries earnings and empowerment, influence their households ability to manage risk. Going beyond the traditional poverty estimates, we use a vulnerability measure which quantifies the welfare loss associated with poverty as well as different types of risks like aggregate and idiosyncratic risks. Applying this measure to an Indian panel survey data for 2000 and 200, we find that SHG members have lower vulnerability as compared to a group of non-SHG (control) members. Furthermore, we find that the poverty contributes to about 80 percent of the vulnerability faced by the household followed by aggregate risk.
urn:nbn:se:uu:diva-12474
Keywords: D14; G21; I32; 330; Microfinance; Vulnerability; Poverty; Risk Coping; Mikrofinanzierung; Armut; Risiko; Niedrigeinkommen; Wirkungsanalyse; Indien